ความเป็นไปได้ในการบริหารจังหวัดปกครองตนเอง - ค้าผล, กรกนก (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 28 No 3 (2560): Academic Services Journal, Prince of Songkla University, 2017)
การวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาและเปรียบเทียบความคิดเห็นของผู้ว่าราชการจังหวัด นายอำเภอ ผู้บริหารองค์กรปกครองส่วนท้องถิ่น และผู้แทนภาคประชาสังคมต่อความเป็นไปได้ในการบริหารจังหวัดปกครองตนเอง 2) ศึกษาแนวทางที่ส่งเสริมความเป็นไปได้ในการบริหารจังหวัดปกครองตนเอง การวิจัยนี้เป็นการวิจัยผสมผสานระหว่างการวิจัยเชิงปริมาณและการวิจัยเชิงคุณภาพ โดยเก็บข้อมูลจากผู้มีส่วนได้ส่วนเสียกับแนวคิดการบริหารจังหวัดปกครองตนเองในจังหวัด ประกอบด้วย ผู้บริหารระดับจังหวัด ผู้บริหารระดับอำเภอ ผู้บริหารองค์กรปกครองส่วนท้องถิ่น (ซึ่งเป็นผู้มีส่วนได้ส่วนเสียจากการบริหารราชการตามรูปแบบจังหวัดปกครองตนเอง) และนักวิชาการผู้เชี่ยวชาญ จำนวน 231 คน การวิเคราะห์ข้อมูลโดยใช้สถิติในการเสนอผลงานวิจัย ซึ่งประกอบด้วย ค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการศึกษาพบว่า 1) ผลการศึกษาและเปรียบเทียบความคิดเห็นต่อความเป็นไปได้ในการบริหารจังหวัดปกครองตนเอง ซึ่งผู้ให้ข้อมูลหลักส่วนใหญ่ดำรงตำแหน่งผู้บริหารองค์กรปกครองส่วนท้องถิ่นโดยเป็นนายกเทศมนตรีในพื้นที่จังหวัดเชียงใหม่ มีความคิดเห็นเกี่ยวกับความเป็นไปได้ในการบริหารจังหวัดปกครองตนเอง โดยภาพรวมอยู่ในระดับมาก และระดับความคิดเห็นที่มีคะแนนเฉลี่ยมากที่สุด ได้แก่ ผู้บริหารองค์กรปกครองส่วนท้องถิ่น มีคะแนนเฉลี่ย 3.86 และระดับความคิดเห็นที่มีคะแนนเฉลี่ยน้อยที่สุด ได้แก่ ผู้ว่าราชการจังหวัด มีคะแนนเฉลี่ย 3.23 2) แนวทางที่ส่งเสริมความเป็นไปได้ในการบริหารจังหวัดปกครองตนเอง พบว่า การกำหนดโครงสร้างการบริหารจังหวัดปกครองตนเอง อันประกอบด้วยสภาจังหวัดปกครองตนเอง ผู้ว่าการจังหวัดปกครองตนเอง และสภาพลเมืองจังหวัดปกครองตนเอง มีความเป็นไปได้มากแต่ต้องศึกษาถึงการกำหนดบทบาทของอำนาจและหน้าที่ที่ชัดเจน โดยกำหนดหลักการในการจัดระเบียบการบริหาร วิธีการ และความสัมพันธ์ระหว่างหน่วยการปกครองส่วนท้องถิ่นกับหน่วยการปกครองส่วนกลาง โดยปล่อยให้ท้องถิ่นต่างๆ ปกครองตนเอง รัฐบาลเพียงแต่คอยควบคุมดูแลเท่านั้น ส่วนตำแหน่งผู้ว่าการจังหวัดปกครองตนเองควรมีการกำหนดคุณสมบัติตัวบุคคลที่จะลงสมัครรับเลือกตั้งให้ชัดเจน ต้องศึกษาผลดี-ผลเสียระหว่างผู้ว่าราชการจังหวัดจากการแต่งตั้งกับจากการเลือกตั้ง เพื่อกำหนดและตรวจสอบอำนาจอิทธิพลของผู้ได้รับการเลือกตั้ง เพราะอาจจะมีอิทธิพลต่อองค์กรอื่นๆ เพื่อความเป็นธรรม การดูแลความสงบเรียบร้อย และด้านสภาพลเมืองควรต้องคำนึงถึงการกำหนดสัดส่วนของกลุ่มองค์กรให้ครอบคลุมพื้นที่ กำหนดหลักเกณฑ์ที่จะสามารถทำให้เกิดสภาพลเมืองจังหวัดที่มีบทบาทหลากหลาย ทั้งนี้การนำรูปแบบการบริหารจังหวัดปกครองตนเองมาใช้สำหรับการบริหารราชการในจังหวัดขณะนี้ยังไม่มีความเหมาะสม เพราะประชาชนส่วนใหญ่ยังไม่มีความเข้าใจในเรื่องของการจัดการตัวเอง แต่ในบางพื้นที่อาจจะดำเนินการได้โดยจะต้องทำเป็นโครงการนำร่องเพื่อศึกษาข้อดีและข้อควรปรับปรุง เพื่อพัฒนาและวางแผนสำหรับพื้นที่อื่นๆ ต่อไป คำสำคัญ: จังหวัดปกครองตนเอง, การกระจายอำนาจ, ผู้ว่าราชการจังหวัด   This research aimed to; 1) study and compare the opinions of the Governors, the Chief District officers, theAdministrators of Local Administrative Organizations, and representatives of Civil Society on the possibility of managing self-governing provinces; and 2) study the guidelines promoting the possibility of managing self-governing provinces. This research was done with the quantitative and qualitative methods. The researcher specifically studied 231 stakeholders on the concept of managing self-governing provinces consisting of provincial administrators, district administrators, administrators of Local Administrative Organizations (stakeholders on self-governing provinces), and technical officers. The statistics for data analysis consisted of percentage, mean, and standard deviation. The research results showed the followings; 1) According to the results of studying and comparing the opinions on the possibility of managing self-governing provinces, the researcher found that most of key informants who were administrators or mayors of Local Administrative Organizations in Chiang Mai Province considerably expressed the opinions on the possibility of managing self-governing provinces. The Administrators of Local Administrative Organizations expressed the opinions with the highest mean of 3.86. The Governors expressed the opinions with the lowest mean of 3.23.; and 2) As for the guidelines promoting the possibility of managing self-governing provinces, the researcher found that the possibility of determining the structure of managing self-governing provinces consisting of Self-Governing Province Council, Self-Governing Province Governor, and Self-Governing Province Civilian Council was high. However, it was necessary to study determination of the role of power and duties by determining the principles of organizing management, methods, and the relationship between Local Administrative Organization and Central Administrative Organization by letting the Local Administrative Organizations govern themselves under supervision of the government. As for Self-Governing Province Governor, it was necessary to clearly determine the qualifications of Self-Governing Province Governor and study advantages and disadvantages to compare between the appointed Governors and the elected Governors for determining and examining power and influence of elected persons for fairness, peace and order. As for Civilian Council, it was necessary to suitably determine proportion of organizational groups and determine the criteria capable of bringing about Provincial Civilian Council with several roles. Nevertheless, the model of managing self-governing provinces used for public administration was not suitable because most people did not understand an approach of self-governing provinces. However, it could be implemented in some areas in the form of the pilot projects for studying advantages and disadvantages to develop, and planning for other areas. Keywords: self-governing provinces, decentralization, governor